A tiny new species of Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Belitung Island and Southeastern Sumatra, Indonesia - Eprilurahman, Rury; Garg, Sonali; Atmaja, Vestidhia Y.; Alhadi, Farits; Munir, Misbahul; Ubaidillah, Rosichon; Arisuryanti, Tuty; Biju, S. D.; Smith, Eric N.; Hamidy, Amir (Zootaxa, 2021)
A tiny new species of narrow-mouthed frog of the genus Microhyla is described from the island of Belitung and southeastern Sumatra, Indonesia. The most distinctive feature of the new frog is its diminutive adult size, snout-vent length ranging only from 12.3 to 15.8 mm in adult males. Phylogenetic analyses based a fragment of the mitochondrial 16S rRNA gene, along with detailed morphological and acoustic comparison differentiate the new taxon from all known congeners. The new species, formally described as Microhyla sriwijaya sp. nov., is a member of the M. achatina species group and the sister taxon to M. orientalis. It is diagnosable from other congeners by a combination of characters: (1) smaller male snout-vent size < 16 mm; (2) snout obtusely rounded in dorsal view; (3) absence of mid-dorsal line and skin fold; (4) first finger reduced (finger I length less than half of finger II length); (5) dorsum with a prominent dark median mark extending posteriorly, narrow anteriorly near the level of the shoulder and expanding dorsolaterally up to the vent; margins of the dorsal marking concave with broad reddish-brown or orange colouration on either side; (6) foot webbing rudimentary, reaching just up to the first subarticular tubercle on all toes; (7) dorsal skin with prominent tubercles, especially in life; (8) tibiotarsal articulation of adpressed limb reaching beyond the snout tip; and (9) males produce a single type of call with pulsatile temporal structure, calls of relatively short duration ranging between 31.8–62.8 s, with two to three pulses delivered at a rate ranging between 32.2–36.0 pulses per second, and the mean overall dominant frequency of 4.3 kHz. The uncorrected pairwise genetic distances between Microhyla sriwijaya sp. nov. and all other known congeners are > 3.8% for the studied 16S gene fragment. The new species was discovered from wayside rural areas with oil palm plantations at four localities in the small island of Belitung (type locality), and from coffee plantation and secondary forest at Lampung in southeastern Sumatra. It is not known from any protected area and appears to be threatened due to tin mining activity, intensive logging, oil palm, and other commonly practiced agriculture activities.